2013
DOI: 10.1186/1757-2215-6-19
|View full text |Cite
|
Sign up to set email alerts
|

Clinical governance network for clinical audit to improve quality in epithelial ovarian cancer management

Abstract: BackgroundEpithelial ovarian cancer (EOC) is the most lethal gynecological cancer. Several hospitals throughout the region provide primary treatment for these patients and it is well know that treatment quality is correlated to the hospital that delivers. The aim of this study was to investigate the management and treatment of EOC in a Region of the North Italy (Emilia-Romagna, Italy).MethodsA multidisciplinary group made up of 11 physicians and 3 biostatisticians was formed in 2009 to perform clinical audits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 21 publications
1
17
0
3
Order By: Relevance
“…Another sensitive aspect, which is likely consistent with the previous issue, is that almost 40% of patients with ovarian cancer did not receive debulking surgery, mainly for clinical reasons or due to the personal will of the woman. This proportion was similar to that found in a previous Italian study (48%), 18 but higher than that reported from the California Cancer Registry (20%) and from a Dutch study by Vernooij et al 19 (8%). These data should once again raise the question about the risk of a diagnostic delay and the adequacy of initial treatment among these patients, including the appropriateness of the information provided to patients after diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…Another sensitive aspect, which is likely consistent with the previous issue, is that almost 40% of patients with ovarian cancer did not receive debulking surgery, mainly for clinical reasons or due to the personal will of the woman. This proportion was similar to that found in a previous Italian study (48%), 18 but higher than that reported from the California Cancer Registry (20%) and from a Dutch study by Vernooij et al 19 (8%). These data should once again raise the question about the risk of a diagnostic delay and the adequacy of initial treatment among these patients, including the appropriateness of the information provided to patients after diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…One of the key factors in the relationship between volume and care outcomes is thought to be the increased likelihood of those practicing high volume care to adhere to best practice guidelines. Our findings identified evidence to support the relationship between hospital volume, surgeon volume, guideline adherence and outcomes in ovarian cancer care such that higher volume hospitals and surgeons were found to be independently associated with increased survival, as well as increased levels of guideline adherent care [27][28][29][30][31][32][33][34][35][36]. Guideline adherent surgery in ovarian cancer includes complex surgical techniques that a specialist surgeon, such as a gynaecological oncologist, may only achieve competency in though completing a high volume of these surgeries, with the support of a specialist multidisciplinary team in their hospital [15,29].…”
Section: Discussionmentioning
confidence: 52%
“…1 Flow diagram of selection process. Flow diagram outlining the selection process of studies found in the initial search and how studies were excluded, leading to the final 32 studies included in the systematic review studies) [27][28][29][30][31][32][33][34][35][36][37][38] and 3) quality improvement approaches (9 studies) [39][40][41][42][43][44][45][46][47].…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%
“…EOC is the primary reason for death from gynecologic cancer that affects women in the world every year [ 30 ]. Although most patients initially show sensitivity to cisplatin, a few years later the drug-resistant metastatic disease occurs [ 31 , 32 ]. Thus, developing novel anti-tumor therapies that can work alone, or in combination with platinum-based therapy is critical [ 33 ].…”
Section: Discussionmentioning
confidence: 99%